1990
DOI: 10.2307/2328813
|View full text |Cite
|
Sign up to set email alerts
|

How Target Shareholders Benefit from Value-Reducing Defensive Strategies in Takeovers

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Wiley and American Finance Association are collaborating with JSTOR to digitize, preserve and extend access ABSTRACT This paper shows that target shareholders can be made bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 8 publications
1
36
1
Order By: Relevance
“…POTENTIAL SYNERGY, COMPETITION, AND MANAGEMENT RESISTANCE Berkovitch and Narayanan (1993) claimed that if a takeover is motivated by synergy, the target can achieve some of the synergy if it resists the takeover or if there are multiple bidders. In that case, it is assumed that the higher the synergy, the higher the target gain if everything else is the same (see Berkovitch & Khannna, 1990;Berkovitch & Narayanan, 1993;Fishman, 1989;Shleifer & Vishny, 1986). Walkling and Long (1984) showed that managerial resistance to takeovers is determined by their expected wealth changes from the takeover.…”
Section: Factors Affecting Returns Of Target and Bidding Firmsmentioning
confidence: 99%
“…POTENTIAL SYNERGY, COMPETITION, AND MANAGEMENT RESISTANCE Berkovitch and Narayanan (1993) claimed that if a takeover is motivated by synergy, the target can achieve some of the synergy if it resists the takeover or if there are multiple bidders. In that case, it is assumed that the higher the synergy, the higher the target gain if everything else is the same (see Berkovitch & Khannna, 1990;Berkovitch & Narayanan, 1993;Fishman, 1989;Shleifer & Vishny, 1986). Walkling and Long (1984) showed that managerial resistance to takeovers is determined by their expected wealth changes from the takeover.…”
Section: Factors Affecting Returns Of Target and Bidding Firmsmentioning
confidence: 99%
“…As summarized in Table 1, the three motives imply different relations. (See Berkovitch and Khanna, 1990.) The target gains is a function of the total gain, conditional on the takeover motive.…”
Section: Introductionmentioning
confidence: 99%
“…Shleifer and Summers give specific examples of cases where wealth was transferred from employees to shareholders during and after a hostile takeover. 10 See also Berkovitch and Khanna (1990) for a discussion on how target shareholders might benefit from 'value reducing defensive strategies'. 11 See Jarrell, Brickley and Netter (1988) for a summary of defensive measures that do and do not require shareholder approval in the USA.…”
Section: Discussionmentioning
confidence: 99%